Problematika Pendidikan Pada Masa Pandemi Covid-19 di Indonesia - Dzikri Wahyu Ramadhani (Ta'lim : Jurnal Multidisiplin Ilmu, 2022)
The implementation of learning experiences various dynamics of change from time to time. One of them is during the Covid-19 pandemic. The Covid-19 pandemic has changed the order of human life around the world in all fields, especially in the field of education. The purpose of writing this article is to identify various kinds of problems that arise during online learning during the Covid-19 pandemic. This article was written using the literature study method by reviewing research data sources and related references. Learning from home is one of the right methods to keep learning in the midst of these dire conditions. Due to the rapidly changing circumstances, various problems arise in this online learning method, such as lack of preparation and lack of supporting facilities. To overcome the problems that arise, cooperation and awareness are needed between educators, students, parents, guardians, families, and people around to support the success and effectiveness of online learning from home.